(untitled) (Revista Apotheke, 2018)
The objective of this work is to articulate some questions about continuing education in the visual arts for pedagogues. Here, the focus is on discussing questions about teacher education itself, including some historical aspects about how teacher training is being thought about in educational settings; to point out a little of the course of a course of continuous formation realized with teachers of the municipal network of education of the prefecture of Florianópolis / SC; as well as to propose some questions to problematize spheres of teacher training and to try other paths for the continued formation. For this purpose, some theoretical articulations are listed as a means of enhancing discussion and expanding possibilities in educational spaces in concomitance with the presentation of the proposal.